Arloji Sales Information System on Web Based Resty Sarah Store - Hamija Siti Nurlaila Hamija; Budi Rachmadani; Emil Riza Putra (Politeknik Pertanian Negeri Samarinda, 2021)
Technological developments, especially internet-based technology, are increasing, including sales information system technology or commonly called web shops that can be used to purchase products by simply logging into the web. In Indonesia, the development of sales information systems is very reasonable and will continue to increase rapidly with the spread of the internet to all corners of the area. This research is based on the background of the Resty Sarah Store, which records the sale and purchase transactions which are still done manually (recording by book). This is still considered ineffective and inefficient. The purpose of this research is to create a web-based sales information system at Sarah's Resty shop. The expected results of this research are the availability of information system applications that can solve existing problems and provide fast information in making decisions.